Whole genome sequencing-based characterization and determination of quinolone resistance among methicillin-resistant and methicillin-susceptible S. Aureus isolates from patients attending regional referral hospitals in Tanzania - Masoud A. Juma; Happiness Kumburu; Boaz Wadugu; Davis Kuchaka; Mariana Shayo; Patrick Kimu; Livin E. Kanje; Melkiory Beti; Marco van Zwetselaar; Blandina Mmbaga; Tolbert Sonda (BMC Genomics)
Abstract Background The emergence of multidrug-resistant termed Methicillin-resistant Staphylococcus aureus (MRSA) strain, driven by the acquisition of resistance gene mecA imposes a substantial challenge in the treatment and control of their related infections. Although quinolones have historically been effective against both MRSA and methicillin-susceptible S. aureus (MSSA) strains, the rising resistance to quinolones among S. aureus isolates, particularly in MRSA, has severely curtailed their potency and further narrowed down the therapeutic options. This study aimed to determine the burden of MRSA among isolates, as well as their resistance profile, genotypic characterization, and molecular relatedness through the construction of a phylogenetic tree. Materials and methods Archived clinical S. aureus isolates from a descriptive, cross-sectional study involving six regional referral hospitals in Dodoma, Songea, Kigoma, Kitete, and Morogoro in the mainland Tanzania and Mnazi Mmoja in Zanzibar were analyzed. Bacterial identification was performed using both classical microbiology and whole genome sequencing on Illumina Nextseq 550 Sequencer. Species identification was done using KmerFinder 3.2, Multilocus Sequence Typing using MLST 2.0, SCCmec typing using SCCmecFinder 1.2, resistance genes using ResFinder 4.1, and phylogenetic relatedness using CSI Phylogeny 1.4. Results Out of the 140 isolates analyzed, 69 (49.3%) were identified as MRSA, with 57 (82.6%) exhibiting quinolone resistance. Conversely, 71 isolates were identified as MSSA, and none of them exhibited resistance to quinolones. Spa-typing revealed six spa types, with t355, t1476, and t498 being the most common. Moreover, all (69) MRSA were found to carry SCCmec type IV. The isolates exhibited 14 different sequence types (STs). Notably, ST152 was prevalent among MSSA (50 isolates, 70%), while ST8 was the predominant sequence type among MRSA (58 isolates, 84%). The antimicrobial resistance profile revealed at least three horizontally acquired resistance genes, with blaZ, dfrG, tet(K), and aac (6’)-aph (2’’) genes being highly prevalent. Conclusion There is a high genetic diversity among the S. aureus isolates existing in Tanzania regional hospitals, with a concerning burden of quinolone resistance among MRSA isolates. The diversity in resistance genes among MRSA lineages emphasizes the necessity for the development of sustainable antimicrobial stewardship and surveillance to support evidence-based guidelines for managing and controlling MRSA infections in both community and hospital settings.